PERLINDUNGAN HUKUM TERHADAP PEMILIK HAK ATAS TANAH DALAM ERA DIGITALISASI SERTIFIKAT TANAH - Ni Made Trisna Dewi; Sang Ayu Made Ary Kusumawardhani (Jurnal Yustitia, 2026)
The Indonesian government, through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN), has initiated a land digitalization policy as part of the modernization of public services in the agrarian sector. This policy is implemented through Ministerial Regulation of ATR/BPN No. 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities, which governs the issuance of electronic land certificates to replace traditional physical ones. This transformation offers positive impacts in terms of efficiency, transparency, and accessibility of land data. However, it also introduces new legal challenges, particularly regarding the legal protection of land rights holders. This article aims to provide a juridical analysis of the extent to which legal protection is granted to landowners in the digitalization era, focusing on legal certainty, data security, and mechanisms for dispute resolution. Using a normative legal research method and analyzing the provisions of Regulation No. 3 of 2023 along with other related land regulations, this study finds that while electronic certificates are legally recognized, several potential risks remain—such as data breaches, system errors, and limited digital literacy among citizens. Therefore, it is crucial to strengthen regulatory frameworks, improve digital security systems, and conduct comprehensive public outreach to ensure that the rights of landowners are fully protected. The study recommends that the digital transformation of land administration be implemented gradually, inclusively, and accountably, accompanied by continuous policy development and strict oversight. Thus, land digitalization can serve not only as a tool for administrative modernization but also as a means to reinforce justice and legal certainty for all land rights holders in Indonesia. Keywords: Legal protection, Land rights, Digitalization, Electronic certificates, Ministerial Regulation of ATR/BPN No. 3 of 2023